2022
DOI: 10.1016/j.oooo.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Loss of FANCD2 and related proteins may predict malignant transformation in oral epithelial dysplasia

Abstract: Background: Predicting malignant transformation in oral epithelial dysplasia(OED) is a clinical challenge. The higher rate of malignant transformation in non-smokers supports an endogenous aetiology. Loss of FANCD2 and associated proteins could lead to genomic instability and oncogenesis.Patients & Methods: Longitudinal archival samples from 40 individuals with OED from time of diagnosis to the most recent review in 23 stable OED; or until excision of the SCC in 17 unstable OED undergoing malignant transformat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 49 publications
(33 reference statements)
1
3
0
Order By: Relevance
“…They showed that defects in DNA repair pathways, specifically decreased expression of BRCA1/BRCA2 and MMR (MLH1, PMS2, MSH2, MSH6) genes, are associated with malignant transformation in OPMD. These findings are supported by Ho et al [74], who demonstrated that decreased expression of other components of the HR pathway (FANCD2, FANCG) were associated with malignant transformations in oral epithelial dysplasia; decreases in the phosphorylation of pFANCD2, pFANCG, pATR and pCHK-1 were also documented [74]. The transition of oral leukoplakia to OSCC in tissues of Indian origin has also been shown to be associated with defects in nucleotide excision repair, base excision repair, and mismatch repair [75].…”
Section: Repairsupporting
confidence: 85%
“…They showed that defects in DNA repair pathways, specifically decreased expression of BRCA1/BRCA2 and MMR (MLH1, PMS2, MSH2, MSH6) genes, are associated with malignant transformation in OPMD. These findings are supported by Ho et al [74], who demonstrated that decreased expression of other components of the HR pathway (FANCD2, FANCG) were associated with malignant transformations in oral epithelial dysplasia; decreases in the phosphorylation of pFANCD2, pFANCG, pATR and pCHK-1 were also documented [74]. The transition of oral leukoplakia to OSCC in tissues of Indian origin has also been shown to be associated with defects in nucleotide excision repair, base excision repair, and mismatch repair [75].…”
Section: Repairsupporting
confidence: 85%
“…The performances of both models were comparable, with the MLA slightly outperforming the PCA-LDA. Both approaches result in substantial improvements over the 40% obtained from current gold standard techniques [ 7 ]. The parity in scores may indicate that both approaches are close to optimal.…”
Section: Discussionmentioning
confidence: 99%
“…Both approaches have a predictive accuracy of ∼80% which has important implications for diagnosis and therapy. Current approaches are only able to make this prediction with an accuracy of 25%–40% [ 7 ] and so fail 60% of patients. This leads to over treatment, requiring unnecessary and painful biopsies, or under treatment resulting in delays to necessary surgery.…”
Section: Discussionmentioning
confidence: 99%
“…However, levels of Chk-2 expression do not correlate with the degree of OED, suggesting that it may be regulated differently [ 128 ]. Significantly reduced levels of expression of phosphorylated ATR and Chk-1 have been observed in patients with OED progressing to OSCC [ 129 ]. Taken together, there are limited studies suggesting an inconsistent pattern of both upregulation and downregulation of DNA repair molecules.…”
Section: Nuclear Biomarkersmentioning
confidence: 99%